Effects of modeled ionospheric conductance and electron loss on self‐consistent ring current simulations during the 5–7 April 2010 storm. Issue 7 (6th July 2015) - Chen, Margaret W.; Lemon, Colby L.; Guild, Timothy B.; Keesee, Amy M.; Lui, Anthony; Goldstein, Jerry; Rodriguez, Juan V.; Anderson, Phillip C.
Abstract We investigate the effects of different ionospheric conductance and electron loss models on ring current dynamics during the large magnetic storm of 5–7 April 2010 using the magnetically and electrically self‐consistent Rice Convection Model–Equilibrium (RCM‐E). The time‐varying RCM‐E proton distribution boundary conditions are specified using a combination of TWINS 1 and 2 ion temperature maps and in situ THEMIS and GOES spectral measurements in the plasma sheet. With strong electron pitch‐angle diffusion, the simulated equatorial ring current electron pressure is weak with (1) uniform conductance or (2) conductance based on parameters from the International Reference Ionosphere 2007 and the feedback of simulated precipitating electrons. With the Chen and Schulz electron loss model that includes strong diffusion in the plasma sheet and weak diffusion in the plasmasphere, the stormtime equatorial RCM‐E electron pressure is enhanced in the inner magnetosphere from midnight through dawn to the dayside. The enhancement extends to lower geocentric distance with uniform conductance than with the more realistic ionospheric conductance model due to electric field shielding effects. Electron losses affect not only the simulated electron pressures, but through magnetospheric‐ionospheric coupling, the redistributed electric and magnetic fields affect the ring current proton transport. The simulations reproduced features observed by in situ magnetic field and proton flux data, and TWINS global ENA observations. The simulated stormtime ring current energization can vary significantly depending on the ionospheric conductance and electron loss model used. Thus, it is important to incorporate realistic descriptions of ionospheric conductance and electron losses in inner magnetospheric models.